Psychosocial Development in Adolescence 2019
DOI: 10.4324/9781315165844-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic system perspectives on anxiety and depression

Abstract: Anxiety and depression disorders are the biggest mental health hazards of our time and in many ways closely related. The first anxiety disorder episodes emerge during childhood, while the first depression episodes more typically emerge in adolescence. Such early episodes are highly predictive for lifespan developments. This chapter reviews literature on dynamic system perspectives on anxiety and depression across scales of temporal resolution, from affect and highly contextualized emotion episodes to more pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 150 publications
2
29
0
Order By: Relevance
“…Emotional blunting processes seem slightly pronounced over lag 2 and 3 ( Figure 2). Given these results cluster 4 people are likely to be characterised by high neuroticism scores (Jeronimus, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…Emotional blunting processes seem slightly pronounced over lag 2 and 3 ( Figure 2). Given these results cluster 4 people are likely to be characterised by high neuroticism scores (Jeronimus, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…In clinical psychology, intensive monitoring of psychopathological symptoms has allowed researchers to examine symptoms’ variability, autocorrelations and other indicators of dynamics during interventions. This has yielded considerable advances in the prediction of phase transitions between adaptive and maladaptive psychological states [ 58 , 126 , 127 , 128 ]. A conceptual replication in a population undergoing a weight loss intervention [ 129 ] recently found that sudden drops in physical activity levels could be predicted by the emergence of erratic fluctuations in day-to-day physical activity.…”
Section: Empirical Solutionsmentioning
confidence: 99%
“…A number of dynamic system approaches focusing on the closely related fields of personality dynamics (Cervone, 2005;Fajkowska, 2015;Jeronimus, 2019;Nowak, Vallacher, & Zochowski, 2005;Pervin, 2001;Read et al, 2010;Richardson, Dale, & Marsh, 2014;Sosnowska, Kuppens, De Fruyt, & Hofmans, 2019;Vallacher, Michaels, & Nowak, this volume), affective dynamics (Hollenstein et al, 2013;Kuppens, Oravecz, & Tuerlinckx, 2010;Kuppens, & Verduyn, 2017), and social interaction dynamics (Hollenstein & Lewis, 2006;Gottman, Murray, Swanson, Tyson, & Swanson, 2003;Pennings et al, 2014) have been introduced in recent years. Some of these approaches already provide mathematically formalized generic models of how personality systems stabilize and change and that show clear links to the social interaction dynamics outlined in this chapter.…”
Section: Personality and Social Interaction 49mentioning
confidence: 99%